Coxsackie Virus A16 Infection of Placenta with Massive Perivillous Fibrin Deposition Leading to Intrauterine Fetal Demise at 36 Weeks Gestation. (July 2015) - Yu, Weiming; Tellier, Raymond; Wright, James R.
Massive perivillous fibrin deposition (MPFD) is an uncommon placental disorder, associated with significant fetal morbidity, mortality, and recurrence; its etiology is unknown. We describe a 31-year-old mother, diagnosed with Coxsackievirus infection and hand-foot-and-mouth disease at 35 weeks gestation. Ultrasound at 35 weeks revealed a normal fetus and placenta. One week later, the mother experienced decreased fetal movement and ultrasound demonstrated intrauterine demise. The autopsy showed mild, acute pericarditis and hypoxic-ischemic encephalopathy. Placenta examination showed MPFD involving 80% of the parenchyma. Molecular viral analysis and serotyping showed Coxsackie A16 virus. The mother had an uneventful pregnancy 15 months later. Coxsackievirus infections in pregnant mothers are often asymptomatic. Transplacental Coxsackievirus infection is very rare but is associated with spontaneous abortion, intrauterine demise, or serious neonatal morbidity. Mild, nonspecific histologic changes have been reported in the placenta. To our knowledge, this is the first report of MPFD associated with Coxsackievirus infection.